Study of Role for Allium Sativum L. and Melatonin in Reduce Methotrexate Side Effect on Normal Male Rabbets - S. Al-Tamimi, Abdul-Haleem; Lahmood Al-obaidi, Wedad M.; A. Al-Jabre, Sadiq (Iraqi Journal of Science, 2023)
This study was to evaluate the role of garlic and melatonin in the reduction of the toxic effect of the drug methotrexate with concentrations 0.52 mg/ kg of body weight of rabbits on total count of white blood cells and enzymes liver functions, used in this study (90) of the male rabbits ,were randomly divided into five groups, six rabbits in each group, given all the animals normal food during the experimental period of 30 days, explained to the animals at the end of each period of experience and took blood samples to count white blood cells, measure liver function enzymes like Aspartate aminotransferase (AST), Alanine aminotransferase(ALT), Alkaline phosphatase (ALP), was reached the following conclusions: (1) The treatment of male rabbits with methotrexate reduced the rate of white blood cells, compared with a negative control and other experimental groups in the first week, but for the observed improvement in the levels of the number of white blood cells (WBCS) in the aggregates experimental treatment in addition to methotrexate, garlic and melatonin. (2)The treatment of animals by methotrexate alone showed an increase in enzyme levels (AST) ,(ALT) and (ALP) while there was a decrease in enzyme levels in treated experimental animals by methotrexate addition to both the garlic and melatonin levels with high spirits. (3) Thus, it can be said that the injection of garlic extract with dose 6 mg/kg of body weight of rabbets, hormone melatonin had a preventive role in reducing the side effects of methotrexate in the number of total white blood cells and activity of hepatic enzymes.